LEXICAL LAYER TAGGING IN THE CORPUS OF NUSRATULLA JUMAKHOJA’S WORKS (World Bulletin of Social Sciences, 2025)
The development of authorial corpora has become a vital branch of corpus linguistics, enabling the exploration of idiolectal features, stylistic peculiarities, and lexical richness of individual authors. This study focuses on the corpus of works by Nusratulla Jumakhoja, a distinguished Uzbek literary scholar and writer, whose texts represent a unique blend of philological analysis, literary criticism, and cultural discourse. The aim of the research is to examine the issues of lexical layer tagging in the construction of his authorial corpus. The methodology includes corpus compilation, annotation at the lexical level, and classification of tokens into major lexical categories such as standard vocabulary, dialectal words, historical lexemes, borrowings, terminological units, and occasionalisms. The study also discusses challenges in tagging caused by polysemy, synonymy, and stylistic variation. Preliminary results indicate that Jumakhoja’s works demonstrate a high frequency of historical and literary vocabulary, alongside a noticeable presence of occasional coinages that highlight his idiosyncratic style. The paper argues that lexical tagging not only ensures systematic corpus analysis but also provides valuable insights into the semantic and stylistic layers of an author’s idiolect. The findings contribute to corpus linguistics, lexicography, and Uzbek literary studies, offering a framework for future computational and comparative research.